The Elements of Nursing : A Model for Nursing Based on a Model of Living - Roper, Nancy; Logan, Winifred W. and Tierney, Alison J. (UK Churchill Livingstone, 1990)
This revised and updated edition is not a comprehensive text covering all aspects of nursing knowledge and practice, but rather it encourages a logical mode of thinking about nursing in the framework of a model for life
Include illustrations, graph and index
Keywords: Nursing -- Roper-Logan-Tierney model for nursing